2010
DOI: 10.1002/uog.7576
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord cysts in the second and third trimesters: significance and prenatal approach

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 34 publications
1
67
0
2
Order By: Relevance
“…In 2010, Zangen et al [7] suggested that the strong association between cysts of the umbilical cord observed during the second and third trimesters of pregnancy and aneuploidy in the literature is biased mainly toward the tendency to report abnormal cases. The case reported here may support this recent hypothesis [7].…”
Section: Discussionmentioning
confidence: 97%
“…In 2010, Zangen et al [7] suggested that the strong association between cysts of the umbilical cord observed during the second and third trimesters of pregnancy and aneuploidy in the literature is biased mainly toward the tendency to report abnormal cases. The case reported here may support this recent hypothesis [7].…”
Section: Discussionmentioning
confidence: 97%
“…Sepulveda et al reported that seven (70%) of ten fetuses with umbilical cord pseudocysts had chromosomal abnormalities [2]. In contrast, Zangen [9] et al recently reported about 10 cases of umbilical cord cysts in the second and third trimesters. Eight of ten cases showed normal neonatal outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence, in the first trimester, is 0.4-3.4% and should lead to the suspicion of patent urachus [2,6]. Color flow imaging is used to identify the umbilical vessels surrounding the umbilical cyst, confirming that it is an allantoic cyst and not a pseudocyst [7,8]. Prenatal ultrasound findings of patent urachus consist in anechoic proximal cord cyst communicating with the bladder [5].…”
Section: Discussionmentioning
confidence: 99%